Mnr Smit leer ons iets - I. Venter; S.E. Botha (AOSIS, 1983)
This patient care study of a depressed elderly man, emphasises the satisfaction nurses can get out of nursing the older patient. The danger of suicide when motor retardation lifts, is clearly illustrated.